The role of efflux pumps in Schistosoma mansoni Praziquantel resistant phenotype - Pinto-Almeida, António (2018)
Background: Schistosomiasis is a neglected disease caused by a trematode of the genus Schistosoma that is second only to malaria in public health significance in Africa, South America, and Asia. Praziquantel (PZQ) is the drug of choice to treat this disease due to its high cure rates and no significant side effects. However, in the last years increasingly cases of tolerance to PZQ have been reported, which has caused growing concerns regarding the emergency of resistance to this drug. Methodology/Principal Findings: Here we describe the selection of a parasitic strain that has a stable resistance phenotype to PZQ. It has been reported that drug resistance in helminths might involve efflux pumps such as members of ATP-binding cassette transport proteins, including P-glycoprotein and multidrug resistance-associated protein families. Here we evaluate the role of efflux pumps in Schistosoma mansoni resistance to PZQ, by comparing the efflux pumps activity in susceptible and resistant strains. The evaluation of the efflux activity was performed by an ethidium bromide accumulation assay in presence and absence of Verapamil. The role of efflux pumps in resistance to PZQ was further investigated comparing the response of susceptible and resistant parasites in the absence and presence of different doses of Verapamil, in an ex vivo assay, and these results were further reinforced through the comparison of the expression levels of SmMDR2 RNA by RT-PCR. Conclusions/Significance: This work strongly suggests the involvement of Pgp-like transporters SMDR2 in Praziquantel drug resistance in S. mansoni. Low doses of Verapamil successfully reverted drug resistance. Our results might give an indication that a combination therapy with PZQ and natural or synthetic Pgp modulators can be an effective strategy for the treatment of confirmed cases of resistance to PZQ in S. mansoni.